Theater workshops as a theurapetic device in psycological care centers of Seridó Potiguar- Brazil (Revista Contexto & Saúde, 2025)
Objective: To identify the users of psychosocial Care Centers perception about theater workshops in their treatments. Methodology: Qualitative study. Twelve users participated to the study, belonging to theater groups offered in two towns of Seridó Potiguar. The datas were collected by semi-structured interview between the months of august and october in 2019. The analysis occurred using the IRAMUTEQ software (Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires). In this article are presented two of the three built categories derived from the findings: the dimension from the mental disorder of the theater perspective; talking and acting freely: the changes in life after the theater. Results: According to the analysis, the categories evoke the theater paper in the comprehension of mental disorder, its contributions to in the recognition and management of symptons, the skills and social interaction perception and development being a way that produces new life conceptions, ally to the fight against mental health stigma and marginalization. Conclusion: the users realize the theater as a valid therapy, exemplifying the transformations occurred in their lives after the participation in the workshops.
Keywords: Art therapy; Mental health; Group Practice; Mental Health Services